Análise termográfica da ação do jato de plasma no tratamento de rugas faciais : série de casos clínicos - Barreto Silva de Cerqueira, Carla; Almeida de Carvalho, Mylana; Peixoto Leite, Márcia Maria; Peixoto Medrado, Alena (Revista de Ciências Médicas e Biológicas, 2021)
Individual’s senescence process takes place slowly and continuously beyond generates several changes including skin aging, since the decline in cellular activities. Countless resources have been created over the years, with the goal of stopping and / or reversing the unsightly aspects of the skin caused by this process. Thus, plasma jet, a new therapeutic resource has been used in order to promote rejuvenation through the reduction of wrinkles and expression lines. Objective: To evaluate the pattern of thermal variation of the tissue treated with a plasma jet, using infrared thermography. Methodology: This was a series of clinical cases involving 5 female patients over the age of 40 who had facial wrinkles. Patients were previously evaluated and anesthetized. Then, plasma jet therapy was performed in the supra-orbital region. Patients were evaluated for thermal imaging before and after anesthesia and post-therapy. Result: It was found through thermographic analysis, a significant variation in the temperature coefficient of the skin where the anesthetic was applied and then the plasma jet (ΔT > 0.4 °C). Conclusion: The present study proved through the use of thermography that the plasma jet was able to generate an increase in local temperature. The authors suggest that such thermal variation may be the result of a process of vasodilation in the treated region.